Parents and Internet: What kind of usage? - Santos, Sandra R. (2018)
The present study aims to evaluate the efficiency of Portuguese parents to use the internet and the resources available as a source of educational support for their children’s education. Our sample was composed of 282 parents (mothers and fathers) whom answered an online survey. The results have shown that there are some differences between socioeconomic groups towards internet access, as well as differences in parental proficiency according to age, socioeconomic and educational levels. The younger mothers, from the highest socioeconomic and educational levels with younger children, are the largest users and the most proficient ones using the Internet for the search of educational information. These results allow us to understand parents’ habits of internet usage and evaluation, which can give us some clues for new researches and to develop new online resources. These findings can help us think of a way to outline the difficulties within lower socioeconomic population in terms of access to information and its evaluation.